The Chernivtsi School for the Study of Traditional Plots and Images - Dzyk, Roman; Paranyuk, Dan (Zagadnienia Rodzajów Literackich, 2023)
The article under discussion deals with the issues of formation and development of the Chernivtsi School of studying traditional plots and images in arts (TPI). It determines the significance of TPI as a constituent of comparative literary studies, as well as outlines the basic ideas of the Chernivtsi TPI School (along with Kyiv and Ternopil centers) in terms of modern Ukrainian comparative studies. The article also reconstructs the background of the formation of the Chernivtsi TPI School since the foundation of the Department of World Literature in the University of Chernivtsi. Particular emphasis has been placed on the activities of Mykola Hulia, Roman Volkov, Oleksandr Biletskyi, Olha Hulia, on the final design of the TPI scientific school, and on the leading role of Anatoliy Volkov in its emergence and functioning (through his own works, publications in co-authorship, supervision of PhD theses). In addition, the article draws peculiar attention to scientific periodicals (“Problems of Literary Criticism” and other educational-methodological editions), summarizes the main accomplishments of the Chernivtsi TPI School (presented by the Lexicon of General and Comparative Literary Studies, 2001 and the collective monograph Traditional Plots and Images, 2004), as well as outlines the heredity of contemporary scholastic research of Chernivtsi literary critics with the Chernivtsi TPI School.